2018
DOI: 10.1007/s11910-018-0890-y
|View full text |Cite
|
Sign up to set email alerts
|

Novel Imaging Biomarkers for Huntington’s Disease and Other Hereditary Choreas

Abstract: Purpose of the ReviewImaging biomarkers for neurodegenerative disorders are primarily developed with the goal to aid diagnosis, to monitor disease progression, and to assess the efficacy of disease-modifying therapies in support to clinical outcomes that may either show limited sensitivity or need extended time for their evaluation. This article will review the most recent concepts and findings in the field of neuroimaging applied to Huntington’s disease and Huntington-like syndromes. Emphasis will be given to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 146 publications
0
10
0
1
Order By: Relevance
“… 21 Spectroscopy and brain positron emission tomography scans might provide a promising biomarker by enabling the early detection of abnormal striatal glucose metabolism. 22 Studies demonstrated that these neuroimaging changes occurred before the emergence of clinical symptoms. 23 Nevertheless, not much is known about typical MRI findings in JHD.…”
Section: Discussionmentioning
confidence: 99%
“… 21 Spectroscopy and brain positron emission tomography scans might provide a promising biomarker by enabling the early detection of abnormal striatal glucose metabolism. 22 Studies demonstrated that these neuroimaging changes occurred before the emergence of clinical symptoms. 23 Nevertheless, not much is known about typical MRI findings in JHD.…”
Section: Discussionmentioning
confidence: 99%
“…Although considerable progress has been made towards identifying some of the mechanisms involved in the HD pathogenesis, there are currently no disease-modifying strategies available [6]. The uncovering of the huntingtin (htt) mutation in 1993 has enabled intensified research efforts with the hope to slow down or stop progressive neuronal damage [4]. HD is an autosomal dominant disease of the central nervous system (CNS) caused by an expansion of the CAG sequence in the huntingtin gene (HTT), located on chromosome 4 [3,7].…”
Section: Huntington's Diseasementioning
confidence: 99%
“…It has been proposed that a flawed proteostasis network results from the aggregation of mHTT, initiating a cascade of devastating consequences for synchronised neuroreceptors [8]. Individuals with 7-12 CAG tracts are usually considered healthy, whilst those with 35 suffer from HD [4]. Additionally, full penetrance and consequently, rapid progression of the disease, is associated with more than 40 repeats [9].…”
Section: Huntington's Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Positron emission tomography (PET) is an imaging modality with high sensitivity and specificity for biochemical markers and metabolic processes in vivo [ 1 ]. It is an important tool in the study of psychiatric and neurological diseases, as well as for evaluating novel and established pharmacological treatments [ 2 4 ]. In PET imaging, study participants receive an intravenous injection of a radioligand, which binds specifically to a target molecule [ 5 ].…”
Section: Introductionmentioning
confidence: 99%